Associations of different dietary patterns, bone mineral density, and fracture risk among elderly women: the China Osteoporosis Prevalence Study - Zhao, Nan; Yin, Xiangjun; Chen, Lin; Tang, Shunyu; Lin, Hua; Cui, Lu; Jin, Xiaolan; Xie, Zhongjian; Jiang, Ning; Cui, Lijia; Yu, Wei; Cummings, Steven R.; et al. (Frontiers in Endocrinology, 2024)
Objective: With one-fifth of the world’s population, higher proportion of elderly, and higher prevalence of osteoporosis and fracture in China, limited studies have been investigated the association between dietary patterns and bone mineral density (BMD) as well as fracture risk among elderly Chinese population. We aimed to investigate the association between different dietary patterns and BMD as well as the risk of fractures, and this association may vary between elderly women and men. Methods: Building upon the China Osteoporosis Prevalence Study, we included 17489 subjects aged≥40 years old randomly sampled across 44 counties/districts of 11 provinces or municipalities in China and completed food frequency questionnaire. BMD was measured by dual X-ray absorptiometry. Vertebral fracture was defined based on lateral spine radiographs using semi-quantitative technique of Genant. Results: A diet rich in “carnivorous”, “vegetarian”, “dairy, fruit, and egg” patterns was significantly associated with higher BMD at total hip (TH), femoral neck (FN), and lumbar spine 1-4 (L1-4). Yet, a diet rich in “beverage and fried food” was associated with lower BMD at FN and L1-4. High quartiles of carnivorous diet were associated with 34%-39% reduced risk of clinical fracture in the past five years and vertebral facture. Stronger associations were observed among women. Sensitivity analysis among postmenopausal women presented even stronger positive associations between carnivorous and vegetarian diets and high BMD, as well as between carnivorous diet and reduced risk of fractures. Conclusions: Our study suggested that a diet rich in carnivorous, vegetarian, and dairy, fruit, and eggs might be associated with higher BMD and lower fracture risk, while beverage and fried foods may be associated with lower BMD at L1-4, especially among elderly women. These findings are relevant to identify recommendation for dietary nutrition regarding the elderly population at high-risk of osteoporosis and fractures, especially for postmenopausal women.